ANALYSIS OF COST AND OUTCOME THERAPY OF BLOOD TRANSFUSION ON ANEMIA TREATMENT FOR INPATIENT WITH CHRONIC RENAL FAILURE - Satibi, Satibi (Indonesian Journal of Pharmacy, 2014)
Chronic Renal Failure (CRF) is a slow progressive loss of kidney function over a period of several years. One of its complications that determines the patient’s quality of life is anemia. Blood transfusion can be used to treat anemia in patient with CRF. The purpose of this study are to measure the average costs per patient, assess the therapy outcomes, and determine the factors that influence the cost of blood transfusion in anemia treatment for patients with CRF in A, B, and C hospitals. This study was a descriptive non-experimental research. Cost analysis was based on the perspective of the hospital. Data were obtained retrospectively from medical records and payment details of inpatient with CRF who experienced anemia in A (tertiery hospital in Yogyakarta province), B (tertiary hospital in Central Java province), and C (private hospital in the province of Yogyakarta) hospitals. Data was analysed by calculating the average costs per patient, while therapy outcome was measured by calculating the percentages of patients who achieved the target of hemoglobin level. Furthermore, the factors that influenced the amount of the total cost were analysed using Oneway ANOVA and Independent T-Test for data with normal distribution and the Kruskal-Wallis and Mann-Whitney for data with non-normal distribution. The results showed that the average costs per patient for anemia treatment in patient with CRF who had blood transfusion therapy were Rp 8,873,243.39±4,417,825.83 in A hospital, Rp 5,249,464.97±4,283,655.41 in B hospital; and Rp 7,961,088.00±6,105,501.80 in C hospital. Most of the patients in A, B, and C hospitals had achieved the target of hemoglobin level (>7g/dL) with the percentages of 95.56%, 68.57% and 87.50% respectively. The factors that mainly influenced the cost of anemia treatment in CRF are length of hospitalization for A hospital, age, gender, payment models, and length of hospitalization for B hospital, whereas age and length of hospitalization for C hospital. Key words: cost analysis, outcome therapy, blood transfusion, anemia, chronic renal failur